Visualized Experiment of Bubble Behaviors in a Vertical Narrow Rectangular Channel Under Natural Circulation Condition - Yan, Meiyue; Ren, Tingting; Chen, Kailun; Yan, Changqi; Yang, Yongyong; Tian, Chunping; Yang, Kuan; Ai, Dechun (Frontiers in Energy Research, 2018)
The characteristics of bubble behavior have been in particular interest for decades due to its significant contribution to understanding the mechanism of heat transfer. In the present work, visualized experiment is conducted to study the bubble characteristics in subcooled flow boiling of a narrow rectangular channel under natural circulation. The experiments were performed at pressures of 0.2 MPa, with inlet subcooling ranging from 20 to 60 K and heat flux ranging from 100 to 300 kW/m2. A high-speed digital camera is used to capture the pictures of bubble behaviors. A sequence of image processing algorithms is used deal with the original bubble images to get relevant bubble parameters. We observe the whole process of a single sliding bubble lifetime and found most of bubbles slide along the heating surface after detaching the nucleation sites. Five typical sliding bubble growth paths are observed in the present experimental conditions. According to the analysis of the experimental data, it can be found that the liquid subcooling and wall superheat are the main factors that affect the bubble size during sliding in narrow rectangular channel under natural circulation condition. Due to the difference of driving force, the sliding velocity of bubble in forced circulation is always larger than that in natural circulation. At the same time, the bubble velocity changes significantly at different heat flux and shooting location.